Causes of unsatisfactory quality of follow-up of patients with arterial hypertension by district therapists - A. E. Manoilov; A. Yu. Markina; O. P. Malykhina (Сибирский научный медицинский журнал, 2025)
Factors affecting the quality of follow-up (FU) of patients with arterial hypertension (AH) have been evaluated in several large-scale studies by Russian scientists. It was found that the indicators of the process and results of medical care for dispensary patients with AH often did not correspond to the conventional benchmark indicators. The purpose of the study was to identify structure, process, and performance indicators that negatively affect the quality of physician FU of AH patients. Material and methods. The study was performed according to the results of 2022. The level of knowledge of doctors, the scheme of the electronic outpatient card, and equipment for ultrasound diagnostics were studied as structural parameters. To assess the process characteristics, information on home blood pressure (BP) monitoring, patients’ adherence to treatment, availability of current analysis of the FU process were used. Performance indicators included information on normalization of BP and lipid level during the year, about stabilization, regression of the degree of left ventricular hypertrophy and carotid atherosclerosis. The sample of respondents, outpatient records was formed by random method. Results. 58.3 % of respondents were not informed about the possibilities of drug therapy to prevent the damaging effect of AH on target organs. The electronic outpatient cards lacked the templates “Follow-up”, “Stage discharge summary”. The available medical equipment met the needs of FUs by about 50 %. Information on home BP monitoring and patients’ adherence to therapy was available in 8.0 % of cases. Current summarization of FU was performed in 10.0 % of patients, assessment of lipid content dynamics, degree of left ventricular hypertrophy and carotid atherosclerosis was not performed in any case. Data on normalization of BP and lipid levels, data on stabilization, regression of left ventricular hypertrophy and carotid atherosclerosis during a year were actually absent. Conclusions. The identified indicators of structure, process and performance of DN are a probable cause of unsatisfactory quality of physician follow-up of AH patients.